Efficient ceramic flat sheet membrane for treating high-turbidity sewage and preparation method of efficient ceramic flat sheet membrane
By using oscillating self-cleaning technology of zirconia toughened alumina ceramics and barium titanate film layers, the problems of low water efficiency and easy equipment damage in high-turbidity sewage treatment are solved, and efficient and continuous sewage treatment and equipment life are achieved.
Patent Information
- Application Number
- CN202510357917.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-06-10
AI Technical Summary
When treating high-turbidity sewage, the water production efficiency is low, the land covers a large area, and the equipment is easily damaged. The backwashing method leads to low water production rate and frequent equipment damage.
Zirconia toughened alumina ceramic is used as the ceramic flat film matrix, and when the barium titanate film layer is oscillated and cleaned by self-cleaning, high-frequency oscillation is generated by barium titanate reverse piezoelectric effect, cleaning is performed while producing water to avoid backwashing.
It improves the service life and water production efficiency of ceramic flat films, reduces equipment damage and operating costs, and achieves efficient and continuous sewage treatment.
Smart Images

Figure CN120115009A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic flat membranes, and more specifically, relates to an efficient ceramic flat membrane for treating high-turbidity sewage and a preparation method thereof. Background Art
[0002] At present, the main methods for treating high-turbidity sewage in China are multi-stage sand filtration or flocculation sedimentation. The turbidity of the water produced by multi-stage sand filtration is still relatively high; flocculation sedimentation occupies a large area and has a low water production efficiency. Although the ordinary membrane technology has a low turbidity of the produced water and a small footprint, whether it is an organic membrane or an inorganic membrane, it requires intermittent backwashing. During backwashing, the water production needs to be stopped, and a large amount of purified water produced is flushed out of the membrane layer through a water pump, and its kinetic energy is used to strip the pollution on the surface of the membrane layer to restore the filtration ability of the membrane layer. This cleaning method not only makes the water production rate of a single water production cycle only 70-85%, but also the electronically controlled valves that are frequently switched are extremely easy to be damaged, resulting in program disorders, and once there are water leakage and motor overload in an unattended site, it will cause huge economic losses. Summary of the Invention
[0003] Aiming at the above problems existing in the prior art, the technical problems to be solved by the present invention are to provide a preparation method of an efficient ceramic flat membrane for treating high-turbidity sewage, using zirconia toughened alumina ceramics as the matrix of the ceramic flat membrane, having better mechanical properties during the oscillating self-cleaning of the barium titanate film layer, and increasing the service life of the ceramic flat membrane; another technical problem to be solved by the present invention is to provide the efficient ceramic flat membrane prepared by the preparation method.
[0004] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0005] A preparation method of an efficient ceramic flat membrane for treating high-turbidity sewage, comprising the following steps:
[0006] 1) Prepare and dry-mix for 5-10 min to form material A according to the ratio of α-alumina: zircon powder: kaolin: sodium carboxymethyl cellulose: PS microspheres = 100: (13-17): (6-10): (4-6): (4-6); prepare and stir to form liquid B according to the ratio of glycerol: water = (2-3): (25-28); continuously spray atomized liquid B into material A while stirring, and continuously mix for 10-15 min to obtain material C;
[0007] 2) Knead and vacuum pug material C to obtain mud material D; extrude mud material D into a mud blank plate through a vacuum extruder, dry the mud blank plate until the moisture content is less than 3%, place it in a kiln furnace, heat it up to 1350-1450 °C, and keep it warm for 3-5 h and then turn off the fire and cool it to obtain the ceramic flat membrane matrix; soak the obtained ceramic flat membrane matrix in anhydrous ethanol and sodium hydroxide solution in sequence and dry it to obtain semi-finished product 1#;
[0008] 3) Prepare and ball mill for 2 - 3 h according to the ratio of nickel basic carbonate: sodium hexametaphosphate: sodium carboxymethylcellulose: PS microspheres: water = 100:(0.5 - 1.5):(0.5 - 1.2):(4 - 6):(168 - 184), and pass through a 200 - mesh sieve to obtain E slurry; spray the E slurry on the surface of the semi - finished product 1# prepared in step 2), control the spraying thickness in the range of 25 - 50 μm, dry after spraying, and paste a small sticker at one corner to obtain semi - finished product 2#;
[0009] 4) Prepare and ball mill for 2 - 3 h according to the ratio of barium titanate: sodium hexametaphosphate: sodium carboxymethylcellulose: absolute ethanol: PS microspheres: water = 100:(0.5 - 1.5):(0.5 - 1.2):2:(4 - 6):(175 - 188), and pass through a 200 - mesh sieve to obtain F slurry; spray the F slurry on the surface of the semi - finished product 2# prepared in step 3), control the spraying thickness in the range of 150 - 200 μm, and dry after spraying to obtain semi - finished product 3#;
[0010] 5) Spray the E slurry on the surface of the semi - finished product 3# prepared in step 4) again, control the spraying thickness in the range of 25 - 50 μm, tear off the small sticker after drying to expose the underlying nickel layer, and send it into a kiln furnace to heat up to 500 - 600 °C, introduce a reducing gas, keep it warm for 1 - 2 h and then heat up to 1150 - 1230 °C, keep it warm for 1 - 2 hours and then extinguish the fire and cool to room temperature to obtain semi - finished product 4#;
[0011] 6) Cut the semi - finished product 4# prepared in step 5) to an appropriate length with a ceramic cutting machine, and perform polarization treatment in a polarization device to obtain semi - finished product 5#; Weld the two wires at the end - sealed inner part of the ceramic flat membrane with circuit sockets to the upper and lower nickel layers of the obtained semi - finished product 5# respectively, and then install and fix them with a sealing resin. The other end of the semi - finished product 5# is installed and fixed with an ordinary ceramic flat membrane end - seal and a sealing resin to obtain a high - efficiency ceramic flat membrane for treating high - turbidity sewage.
[0012] Preferably, in the step 1), the particle size D50 of α - alumina is 8 - 12 μm, and the Al 2 O 3 content ≥ 99%; the particle size D50 of zircon powder is 8 - 12 μm, and the ZrO 2 content ≥ 70%, and the SiO 2 content ≤ 30%; the particle size D50 of kaolin is 5 - 10 μm, and the Al 2 O 3 content ≥ 35%, and the SiO 2 content ≥ 45%; the molecular weight of sodium carboxymethylcellulose is 5000 - 10000; the particle size D50 of PS microspheres is 3 - 5 μm.
[0013] Preferably, in the step 2), the water content of the mud material D is 15.5-16.5%.
[0014] Preferably, in the step 3), the particle size D50 of the PS microspheres is 1 μm.
[0015] Preferably, in the step 3), The small sticker is an easily torn masking paper.
[0016] Preferably, in the step 4), the particle size D50 of barium titanate is 3-5 μm; the particle size D50 of the PS microspheres is 1 μm.
[0017] Preferably, in the step 6), the polarization electric field of the polarization device is 2 kV / mm, the polarization temperature is 40-50 °C, and the polarization time is 15-25 min.
[0018] The ceramic flat membrane is prepared by the method for preparing a high-efficiency ceramic flat membrane for treating high-turbidity sewage.
[0019] The application of the ceramic flat membrane in sewage treatment.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] 1) The present invention uses α-aluminum oxide and zirconium silicate powder with a D50 of 8-12 μm as the main materials of the ceramic flat membrane matrix plate, increasing the matrix pore size and improving the water production efficiency;
[0022] 2) The present invention uses zirconia toughened alumina ceramic as the ceramic flat membrane matrix, which has better mechanical properties during the oscillation self-cleaning of the barium titanate film layer, increasing the service life of the ceramic flat membrane;
[0023] 3) The present invention uses barium titanate particles with a D50 of 3-5 μm as the main material of the film layer, increasing the film layer pore size and improving the water production efficiency without affecting the water production turbidity;
[0024] 4) The present invention uses barium titanate particles as the main material of the film layer of the ceramic flat membrane. On the one hand, it plays the filtering role of a conventional film layer. On the other hand, by utilizing the inverse piezoelectric effect of barium titanate and applying a suitable electric field to it, it generates high-frequency vibrations of 6-8 MHz to peel off the pollutants on the film layer; thus, the membrane module can clean while producing water and does not require backwashing with the produced purified water, greatly improving the water production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic side view of a high-efficiency ceramic flat membrane for treating high-turbidity sewage;
[0026] Figure 2 It is a schematic front view of a high-efficiency ceramic flat membrane for treating high-turbidity sewage;
[0027] Figure 3 It is a working schematic diagram of an efficient ceramic flat membrane for treating high-turbidity sewage. Specific implementation manners
[0028] To make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described below in conjunction with specific embodiments. In the following embodiments, unless otherwise specified, the technical means used are all conventional means well known to those skilled in the art. For those not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. For reagents or instruments not specified by the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0029] Embodiment 1
[0030] As Figure 1 、 Figure 2 shown, the efficient ceramic flat membrane for treating high-turbidity sewage provided by the present invention is composed of a ceramic flat membrane matrix 4, a barium titanate inverse piezoelectric oscillation film layer 2, a first nickel electrode layer 1 and a second nickel electrode layer 3. Among them, the main body of the ceramic flat membrane matrix 4 is zirconia toughened alumina porous ceramic, the main body of the barium titanate inverse piezoelectric oscillation film layer 2 is barium titanate crystal, and the main bodies of the first nickel electrode layer 1 and the second nickel electrode layer 3 are both metallic nickel.
[0031] As Figure 3 shown, the working process of the efficient ceramic flat membrane for treating high-turbidity sewage provided by the present invention is as follows: Immerse the ceramic flat membrane in a sufficient amount of suspension with a certain turbidity, connect one end to a suction pump and the other end to a ceramic oscillation controller, start the suction pump and the ceramic oscillation controller, set the suction pressure to -10 kPa to -20 kPa, and the oscillation frequency to 6 to 8 MHz, and the ceramic flat membrane produces purified water.
[0032] The preparation method of the above-mentioned efficient ceramic flat membrane for treating high-turbidity sewage is specifically as follows:
[0033] 1) Prepare and premix Material A according to the components in Table 1, stir Liquid B evenly, spray Liquid B into Material A by atomized spraying, and stir and mix for 10 to 15 minutes while spraying to obtain Material C. Place Material C in a kneader and knead for 15 to 20 minutes, and then use a vacuum mud mixer to make it into mud D, and the moisture content of mud D is 15.5% to 16.55%;
[0034] Table 1 Components and requirements of Material A and Liquid B
[0035]
[0036] 2) Use a vacuum extruder to extrude the mud material D into a mud blank plate. After drying the mud blank plate in a dryer until the moisture content is less than 3%, send it into a kiln and heat it up to 1350 - 1450 °C, and keep it warm for 3 - 5 h, then extinguish the fire and cool it to obtain a ceramic flat membrane matrix;
[0037] 3) Immerse the ceramic flat membrane matrix in anhydrous ethanol and sodium hydroxide solution in sequence. The mass fraction of sodium hydroxide in the sodium hydroxide solution is 6 - 8% to remove oil and impurity, and place it in a dryer to dry to obtain semi-finished product 1#;
[0038] 4) Prepare according to the composition in Table 2 and place it in a ball mill to ball mill for 2 - 3 hours, and pass through a 200 - mesh sieve to obtain slurry E. Use a high - pressure atomizing device with a spraying pressure of 0.5 MPa to spray slurry E on the surface of semi - finished product 1#, control the spraying thickness in the range of 25 - 50 μm, immediately dry it after spraying, and paste an easily - torn masking paper at one corner to obtain semi - finished product 2#;
[0039] Table 2 Composition and requirements of slurry E
[0040]
[0041] 5) Prepare according to the composition in Table 3 and ball mill and pass through a 200 - mesh sieve to obtain slurry F. Use a high - pressure atomizing device with a spraying pressure of 0.5 MPa to spray slurry F on the surface of the dried semi - finished product 2#, control the spraying thickness in the range of 150 - 200 μm, immediately dry it after spraying to obtain semi - finished product 3#;
[0042] Table 3 Composition and requirements of slurry F
[0043]
[0044] 6) Use the high - pressure atomizing device with a spraying pressure of 0.5 MPa again to spray slurry E on the surface of semi - finished product 3#, control the spraying thickness in the range of 25 - 50 μm, after drying, tear off the masking paper to expose the lower nickel layer, and send it into a kiln to heat up to 500 - 600 °C, introduce a reducing gas, keep it warm for 1 - 2 h, then heat it up to 1150 - 1230 °C, keep it warm for 1 - 2 h, then extinguish the fire and cool it to room temperature to obtain semi - finished product 4#;
[0045] 7) Use a ceramic cutting machine to cut semi - finished product 4# to an appropriate length, send it into a polarization device, set the polarization electric field to 2 kV / mm, the polarization temperature to 40 - 50 °C, and the polarization time to 15 - 25 min to perform polarization treatment on it to obtain semi - finished product 5#;
[0046] 8) First, weld the two wires inside the end seal of the special ceramic flat membrane with a circuit socket to the upper and lower nickel layers of the semi-finished product 5# respectively, and then install and fix them with a sealing resin. Install and fix the other end of the semi-finished product 5# with an ordinary ceramic flat membrane end seal and a sealing resin to obtain a high-efficiency ceramic flat membrane for treating high-turbidity sewage.
[0047] Example 2
[0048] Use the method of Example 1 to prepare a high-efficiency ceramic flat membrane for treating high-turbidity sewage, and conduct performance tests on the product. The specific results are shown in Table 4. Among them, the bending strength of the present invention is tested in accordance with GB / T 6569-1986; the porosity of the product is tested in accordance with the method of GB / T 1966-1996; the average pore size of the product is tested in accordance with the method of GB / T 32361-2015; the test method for the particle removal rate is as follows: prepare a suspension of 180 NTU with clear water and white kaolin, immerse the ceramic flat membrane in it, connect a suction pump, and use a turbidimeter to test the turbidity of the produced purified water. The reduction ratio compared with the suspension is the particle removal rate; the test method for water flux is as follows: immerse the ceramic flat membrane in pure water, connect a suction pump, and test the water production per unit time per unit area under a specified pressure; the test method for the continuous working duration is as follows: immerse the ceramic flat membrane in a sufficient amount of 180 NTU suspension, connect a suction pump at one end and a ceramic oscillation controller at the other end, start the suction pump and the ceramic oscillation controller, start timing, and record the duration until the ceramic flat membrane can no longer produce purified water; the test method for the water production rate is as follows: immerse the ceramic flat membrane in a sufficient amount of 180 NTU suspension, connect a suction pump at one end and a ceramic oscillation controller at the other end, start the suction pump and the ceramic oscillation controller, and measure the ratio of the volume of water in the clean water tank to the flow meter on the peristaltic pump within a certain time as the water production rate.
[0049] Table 4 Product Components and Performance Results
[0050]
[0051] In the table, the D50 of α-aluminum oxide is 12 μm, and the content of Al 2 O 3 is 99.8%; the D50 of zirconium silicate powder is 12 μm, and the content of ZrO 2 is 72.1%, and the content of SiO 2 is 27.3%; the D50 of kaolin is 6 μm, and the content of Al 2 O 3 is 38.3%, and the content of SiO 2 is 46.6%; the molecular weight of sodium carboxymethyl cellulose is 5000 - 10000; the D50 of PS microspheres in material A is 5 μm; the D50 of barium titanate is 3 μm.
[0052] In the present invention, barium titanate is used instead of alumina as the membrane layer of the ceramic flat membrane. By utilizing the inverse piezoelectric effect of barium titanate, an electric field is applied to it to generate high-frequency oscillations, thereby stripping the pollutants on the membrane layer surface. This eliminates the waste of frequently using the produced purified water for backwashing in the traditional membrane modules in the field of high-turbidity sewage treatment, and improves the water production efficiency. At the same time, the present invention also uses zirconia toughened alumina ceramics as the substrate, which improves its service life.
[0053] Comparative Example 1
[0054] Taking the product 1 formula and preparation method of Example 2 as an example to prepare the target product.
[0055] 1) When preparing the F slurry, replace barium titanate with alumina, and keep other components and preparation processes unchanged.
[0056] Comparative Example 2
[0057] Taking the product 1 formula and preparation method of Example 2 as an example to prepare the target product.
[0058] 1) When preparing the A material, adjust the amount of zircon powder from 13 parts to 0;
[0059] 2) When preparing the B liquid, adjust the amount of water from 25 parts to 23 parts
[0060] Table 5 Performance Results of Comparative Example 1 and Comparative Example 2
[0061]
[0062] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art in this technical field, without departing from the principle of the present invention, several improvements and refinements can still be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a high-efficiency ceramic flat membrane for treating high-turbidity sewage, characterized in that: The following steps are involved: 1) Prepare material A in the ratio of α-alumina: zircon powder: kaolin: sodium carboxymethyl cellulose: PS microspheres = 100: (13-17): (6-10): (4-6): (4-6) and dry mix for 5-10 minutes; prepare liquid B in the ratio of glycerol: water = (2-3): (25-28) and stir; continuously spray atomized liquid B into material A while stirring, and continue mixing for 10-15 minutes to obtain material C; 2) Material C is kneaded and vacuum-mixed to obtain clay material D; clay material D is formed into a clay blank by a vacuum extruder, and the clay blank is dried to a moisture content of less than 3%, and then placed in a kiln and heated to 1350-1450°C, and kept warm for 3-5 hours, and then turned off and cooled to obtain a ceramic flat membrane matrix; the obtained ceramic flat membrane matrix is sequentially immersed in anhydrous ethanol and sodium hydroxide solution and dried to obtain a semi-finished product 1#; 3) Prepare the mixture according to the ratio of basic nickel carbonate: sodium hexametaphosphate: sodium carboxymethyl cellulose: PS microspheres: water = 100: (0.5-1.5): (0.5-1.2): (4-6): (168-184) and ball mill for 2-3 hours, and pass through a 200 mesh to obtain an E slurry; spray the E slurry on the surface of the semi-finished product 1# obtained in step 2), control the spraying thickness to be in the range of 25-50 μm, dry it after spraying, and paste a Small stickers get semi-finished product 2#; 4) Prepare barium titanate: sodium hexametaphosphate: sodium carboxymethyl cellulose: anhydrous ethanol: PS microspheres: water = 100: (0.5-1.5): (0.5-1.2): 2: (4-6): (175-188) and ball mill for 2-3 hours, and pass through a 200 mesh to obtain F slurry; spray the F slurry on the surface of the semi-finished product 2# obtained in step 3), control the spraying thickness to be in the range of 150-200 μm, and dry after spraying to obtain semi-finished product 3#; 5) Spray the E slurry again on the surface of the semi-finished product 3# obtained in step 4), control the spraying thickness to be in the range of 25-50μm, tear off the small sticker after drying, send it into the kiln and heat it to 500-600℃, introduce reducing gas, keep it warm for 1-2h, then heat it to 1150-1230℃, keep it warm for 1-2h, turn off the fire and cool it to room temperature to obtain the semi-finished product 4#; 6) Cut the semi-finished product 4# obtained in step 5) into a suitable length using a ceramic cutting machine, and polarize it in a polarization device to obtain a semi-finished product 5#; respectively weld the two wires in the end seal of the ceramic flat membrane with a circuit socket to the upper and lower layers of the obtained semi-finished product 5#, and then fix it with a sealing resin; the other end of the semi-finished product 5# is fixed with an ordinary ceramic flat membrane end seal and a sealing resin to obtain a high-efficiency ceramic flat membrane for treating high-turbidity sewage.
2. The method for preparing a high-efficiency ceramic flat membrane for treating high-turbidity sewage according to claim 1, characterized in that: In the step 1), the particle size D50 of α-alumina is 8-12 μm, and the Al2O3 content is ≥99%; the particle size D50 of zircon powder is 8-12 μm, the ZrO2 content is ≥70%, and the SiO2 content is ≤30%; the particle size D50 of kaolin is 5-10 μm, the Al2O3 content is ≥35%, and the SiO2 content is ≥45%; the molecular weight of sodium carboxymethyl cellulose is 5000-10000; and the particle size D50 of PS microspheres is 3-5 μm.
3. The method for preparing a high-efficiency ceramic flat membrane for treating high-turbidity sewage according to claim 1, characterized in that: In the step 2), the moisture content of the mud material D is 15.5-16.5%.
4. The method for preparing a high-efficiency ceramic flat membrane for treating high-turbidity sewage according to claim 1, characterized in that: In the step 3), the particle size D50 of the PS microspheres is 1 μm.
5. The method for preparing a high-efficiency ceramic flat membrane for treating high-turbidity sewage according to claim 1, characterized in that: In the step 3), The small stickers are easy-to-tear textured paper.
6. The method for preparing a high-efficiency ceramic flat membrane for treating high-turbidity sewage according to claim 1, characterized in that: In the step 4), the particle size D50 of barium titanate is 3-5 μm; the particle size D50 of PS microspheres is 1 μm.
7. The method for preparing a high-efficiency ceramic flat membrane for treating high-turbidity sewage according to claim 1, characterized in that: In the step 6), the polarization electric field of the polarization device is 2 kV / mm, the polarization temperature is 40-50° C., and the polarization time is 15-25 min.
8. The method for preparing a high-efficiency ceramic flat membrane for treating high-turbidity sewage according to any one of claims 1 to 7 to obtain a ceramic flat membrane.
9. Use of the ceramic flat membrane according to claim 8 in sewage treatment.